Role of astral microtubules and actin in spindle orientation and migration in the budding yeast, Saccharomyces cerevisiae (The Rockefeller University Press, 1992)
In the yeast Saccharomyces cerevisiae, before the onset of anaphase, the spindle apparatus is always positioned with one spindle pole at, or through, the neck between the mother cell and the growing bud. This spindle orientation enables proper chromosome segregation to occur during anaphase, allowing one replicated genome to be segregated into the bud and the other to remain in the mother cell. In this study, we synchronized a population of cells before the onset of anaphase such that > 90% of the cells in the population had spindles with the correct orientation, and then disrupted specific cytoskeletal elements using temperature-sensitive mutations. Disruption of either the astral microtubules or actin function resulted in improper spindle orientation in approximately 40-50% of the cells. When cells with disrupted astral microtubules or actin function entered into anaphase, there was a 100- 200-fold increase in the frequency of binucleated cell bodies. Thus, the maintenance of proper spindle orientation by these cytoskeletal elements was essential for proper chromosome segregation. These data are consistent with the model that proper spindle orientation is maintained by directly or indirectly tethering the astral microtubules to the actin cytoskeleton. After nuclear migration, but before anaphase, bulk chromosome movement occurs within the nucleus apparently because the chromosomes are attached to a mobile spindle. The frequency and magnitude of bulk chromosome movement is greatly diminished by disruption of the astral microtubules but not by disruption of the nonkinetochore spindle microtubules. These results suggest that astral microtubules are not only important for spindle orientation before anaphase, but they also mediate force on the spindle, generating spindle displacement and in turn chromosome movement. Potential roles for this force in spindle assembly and orientation are discussed.